Preliminary studies of biosynthesis of heme O and heme A in intraerythrocytic stages of P. falciparum - Simao Gurge, Raquel (2014)
Intermediates of the isoprenoid metabolism can bind to heme groups. Heme is critical and its derivatives, heme O and heme A, are the main compounds of aerobic respiration. They are synthesized by farnesylation of heme groups by ?heme O synthase? (HOS or Cox10) and ?heme A synthase? (HAS or Cox15). The identification of heme O and heme A and characterization of enzymes involved in their synthesis are important for exploring the possible products biosynthesized by the parasite derived from the MEP pathway. Importantly, hemes A and O are essential molecules for numerous living organisms, since they are critical components of the mitochondrial electron transport chain, catalyzing the reduction of O2 to H2O. Additionally, the heme group is an important target of drugs such as artemisinin and quinolines.